Efektivitas Rancang Bangun Alat Fikasasi Pada Pemeriksaan Babygram di Radiologi Rumah Sakit TK.II Pelamonia Makassar - A. Ar. Rakhmansya Iskandar; Wahyu Wahyu (Lembaga Pengembangan Kinerja Dosen, 2024)
A fixation device is a tool used to make it easier for a radiographer to carry out examinations in radiology. Bontranger, 2014 The use of this tool has a specific nature, this tool can only be used for certain examinations, for example the Babygram examination. The aim of this research is to determine the effectiveness of the design and construction of fixation equipment in the Radiology Installation at TK.II Pelamonia Makassar Hospital in March – May 2024. The independent variables in this research are the aspects of equipment feasibility, equipment safety, equipment function and radiographic results. This type of research is Quantitative Descriptive Analytical. The data collection technique uses a questionnaire. The population and sample were 11 respondents, namely 10 radiographers and 3 radiology specialists. The sampling technique was carried out by accidental sampling. Data analysis uses descriptive analysis and is presented in the form of a frequency distribution table. Based on the research results, it can be concluded that the design of the Babygram fixation tool from the feasibility test aspect of the tool was obtained as Very Suitable (100%) for use and Fairly Good (100%) set on the examination table. For the safety aspect test results, the results were quite safe (100%) for supporting the baby and the results were very safe (100%) for the quality of the materials used. Meanwhile, for the test results of whether the tool can be used, the results obtained are very suitable (100%), it can be adjusted and adjusted to the shape and size of the baby's body, but quite a long time (100%) is needed during the examination. The radiographic test results obtained were Very Good (100%) showing anatomical structures and None (100%) showing radiographic results free from artifacts. It is best to have a fixation tool available in Radiology because it really helps radiographers treat non-cooperative patients and with a fixation tool the time required is very faster compared to without using a fixation tool.